2001
DOI: 10.2169/internalmedicine.40.1195
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor in Pulmonary Aspergilloma.

Abstract: Objective Vascular endothelial growth factor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
3
14
2
Order By: Relevance
“…Consistent with previous data that levels of VEGF are significantly elevated in inflammatory disorders, including lung inflammatory disease,6,7,18,19 our present results also demonstrated that VEGF levels were increased in inflammatory lung diseases, such as bronchiectasis, aspergilloma, post-tuberculosis destroyed lung, and pneumonia, when compared with published normal values 20,21. Additionally, elevated VEGF levels correlated with severity of inflammation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous data that levels of VEGF are significantly elevated in inflammatory disorders, including lung inflammatory disease,6,7,18,19 our present results also demonstrated that VEGF levels were increased in inflammatory lung diseases, such as bronchiectasis, aspergilloma, post-tuberculosis destroyed lung, and pneumonia, when compared with published normal values 20,21. Additionally, elevated VEGF levels correlated with severity of inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…The required sample size was calculated based on VEGF levels according to the presence of hemoptysis in patients with asperilloma 6. Assuming 437±164 pg/mL of VEGF in the hemoptysis group and 162±102 pg/mL in the no hemoptysis group, a sample size of 42 patients (21 per group) was required to detect a 120 pg/mL difference between the two groups with a power of 90% and α error of 0.05 using a two-tailed test 17.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF is one of the predictive serum markers for the likelihood of developing hemoptysis. 11 However, results of from our study were not in consistence with previous report regarding hemoptysis. In our study, VEGF level not in serum, but in BALF was measured, and we did not find any correlation between BALF VEGF levels and the presence of hemoptysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, Aspergillus clavatus secretes cytochalasin E, which is a potent and selective inhibitor of capillary endothelial cell proliferation in an experimental model (16). On the other hand, it has been shown that in patients with aspergillomas, the levels of vascular endothelial growth factor (VEGF) in serum were raised, and the level was related to the area of lung involvement, PaO 2 level, and the presence of hemoptysis (8). Furthermore, the expression of VEGF was high in alveolar macrophages in the lesion of aspergillomas, and VEGF expression in macrophages was induced by hypoxia and lactate and its expression promoted angiogenesis and increased vascular permeability (5,19).…”
Section: Discussionmentioning
confidence: 99%